Inside and out of painting - Pasta, Paulo (PORTO ARTE: Revista de Artes Visuais, 2013)
In this essay, the painter Paulo Pasta seeks to tell a story from within his own work; that is, from the forms he used as motivation of his painting, the author points to the main questions that made his experience. A relation mediated by the making, in which he seeks precisely to build a reflexive distance between the project and the real experience of painting.